An Experimental Study on Regulated and Unregulated Pollutants from a Spark Ignition Car Fuelled on Liquefied Petroleum Gas and Gasoline: Pollutants from LPG/Gasoline Cars - Shah, Asad Naeem; shan, G.E. Yun-; Gardezi, Syed Asad Raza; fang, WANG Jun-; Jian-wei, TAN (Biological Sciences - PJSIR, 2010)
In the experimental study conducted on a spark ignition (SI) car running on a chassis dynamometer, fuelled on liquefied petroleum gas (LPG) and gasoline, carbon monoxide (CO) and total hydrocarbons (HC) decreased by 37.3% and 46.8%, respectively, while oxides of nitrogen (NOx) increased by 59.7% due to higher compression ratio with LPG, compared with gasoline. In case of LPG fuel, formaldehyde, acetaldehyde, propionaldehyde, 2-butanone, butyraldehyde, benzaldehyde and valeraldehyde decreased, leading to an over all decrease of about 35% and 26% in carbonyls and their ozone forming potential (OFP), respectively, compared with gasoline. Furthermore, benzene, toluene, ethyl benzene, xylene and styrene decreased, resulting in an overall decrease of 38.8% in volatile organic compounds (VOCs) and 39.2% in BTEX (benzene, toluene, ethyl benzene and xylene) species due to more complete combustion with LPG, compared with gasoline. Further, the OFP of VOCs with LPG was 6% lower than that with gasoline fuel.